2011
DOI: 10.1167/iovs.10-5593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photodynamic Therapy on Rapidly Growing Nontuberculous Mycobacteria Keratitis

Abstract: This study demonstrated the effectiveness of MB-mediated PDT against Mycobacterium fortuitum. PDT could be a potential alternative treatment for nontuberculous mycobacterial corneal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 27 publications
0
25
0
1
Order By: Relevance
“…in 2011, it has been found that in vitro after PDI treatment at 100 J cm −2 with 10 −3 % MB, the bacterial count of mycobacteria keratitis had a 2log reduction immediately. While concentration of MB was increased to 10 −2 %, almost no viable bacteria were detected after PDI treatment . MB is also renowned for efficiently eliminating a wide range of microorganisms .…”
Section: Photosensitizers In Photodynamic Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…in 2011, it has been found that in vitro after PDI treatment at 100 J cm −2 with 10 −3 % MB, the bacterial count of mycobacteria keratitis had a 2log reduction immediately. While concentration of MB was increased to 10 −2 %, almost no viable bacteria were detected after PDI treatment . MB is also renowned for efficiently eliminating a wide range of microorganisms .…”
Section: Photosensitizers In Photodynamic Inhibitionmentioning
confidence: 99%
“…While concentration of MB was increased to 10 −2 %, almost no viable bacteria were detected after PDI treatment. [ 85 ] MB is also renowned for efficiently eliminating a wide range of microorganisms. [ 86 ] The addition of cationic ammonium species in MB derivatives was found by Andreas Späth group in 2013 to lead to better PDI efficiency in the following order tertiary > secondary > primary ammonium groups.…”
Section: Phenothiazinium Chromophorementioning
confidence: 99%
“…PDT studies on TB have been focused on the homologous system M. bovis Bacille Calmette Guerin (BCG) both in vitro applying phenothiazinium salts and in murine models of localized mycobacterial induced granulomatous formation [51,52]. In a similar fashion, the antimicrobial effects of PDT have been assessed on infections caused by M. marinum [53] and on rapidly growing nontuberculous mycobacteria keratitis [54]. …”
Section: Photodynamic Therapy As An Anti-infectivementioning
confidence: 99%
“…To date, only little experimental evidence is provided, whether PDI is a useful option to fight bacterial keratitis. In 2011, Shih et al 39. demonstrated the bactericidal efficiency of a combination of the antibiotic amikacin and PDI with the photosensitizer methylene blue (MB) and red light (λ = 650 nm) in a rabbit model of Mycobacterium fortuitum keratitis.…”
mentioning
confidence: 99%